Dopant profiling in silicon nanowires measured by scanning capacitance microscopy. Issue 4 (17th March 2014) - Bassani, Franck; Periwal, Priyanka; Salem, Bassem; Chevalier, Nicolas; Mariolle, Denis; Audoit, Guillaume; Gentile, Pascal; Baron, Thierry
Abstract Silicon nanowires (SiNWs) with axial doping junctions were synthesized via the Au‐catalyzed vapor–liquid–solid growth method with the use of HCl. In this work, dopant profiling from three axially doped SiNWs with p–i, p–n and n–i–p junctions were investigated using both scanning electron microscopy (SEM) and scanning capacitance microscopy (SCM). It turns out that observed doping contrasts in SEM are also affected by the surface roughness and sample charging. In contrast, SCM allows us to delineate with sub‐10 nm resolution the electrical junctions and provides a relative value of the doping concentration in each segment of the NW. SCM clearly evidences the expected doping regions within these SiNWs thanks to the addition of HCl during the growth that strongly prevents shell overgrowth. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)